Age-related impairments in skeletal muscle PDH phosphorylation and plasma lactate are indicative of metabolic inflexibility and the effects of exercise training - Consitt, Leslie A. (Am J Physiol Endocrinol Metab, 2016)
The purpose of this study was to determine whether plasma lactate and skeletal muscle glucose regulatory pathways, specifically PDH dephosphorylation, are impaired during hyperinsulinemic conditions in middle- to older-aged individuals and determine whether exercise training could improve key variables responsible for skeletal muscle PDH regulation. Eighteen young (19–29 yr; n = 9 males and 9 females) and 20 middle- to older-aged (57–82 yr; n = 10 males and 10 females) individuals underwent a 2-h euglycemic hyperinsulinemic clamp. Plasma samples were obtained at baseline and at 30, 50, 90, and 120 min for analysis of lactate, and skeletal muscle biopsies were performed at 60 min for analysis of protein associated with glucose metabolism. In response to insulin, plasma lactate was elevated in aged individuals when normalized to insulin action. Insulin-stimulated phosphorylation of skeletal muscle PDH on serine sites 232, 293, and 300 decreased in young individuals only. Changes in insulin-stimulated PDH phosphorylation were positively related to changes in plasma lactate. No age-related differences were observed in skeletal muscle phosphorylation of LDH, GSK-3α, or GSK-3β in response to insulin or PDP1, PDP2, PDK2, PDK4, or MPC1 total protein. Twelve weeks of endurance- or strength-oriented exercise training improved insulin-stimulated PDH dephosphorylation, which was related to a reduced lactate response. These findings suggest that impairments in insulin-induced PDH regulation in a sedentary aging population contribute to impaired glucose metabolism and that exercise training is an effective intervention for treating metabolic inflexibility.